2008
DOI: 10.1038/ja.2008.86
|View full text |Cite|
|
Sign up to set email alerts
|

Methyl Glucosyl-3,4-dehydro-apo-8′-lycopenoate, a Novel Antioxidative Glyco-C30-carotenoic Acid Produced by a Marine Bacterium Planococcus maritimus

Abstract: Planococcus maritimus strain iso-3 was isolated from an intertidal sediment sample from the Clyde estuary in the UK. A novel red pigment glyco-carotenoic acid ester, methyl glucosyl-3,4-dehydro-apo-8Ј-lycopenoate has been isolated from this marine bacterium using chromatographic methods. The structure of methyl glucosyl-3,4-dehydro-apo-8Ј-lycopenoate was determined to be methyl 1-(b -D-glucopyranosyloxy)-3,4-didehydro-1,2-dihydro-8Ј-apo-y -caroten-8Ј-oate by the degradation experiment and the spectroscopic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] These studies have reported the isolation of rare carotenoids, (3R)-saproxanthin and myxol, from Flavobacteriaceae, 7 and novel glyco-C 30 carotenoids (diapolycopenedioic acid xylosyl esters A, B, and C from Rubritalea squalenifaciens 8 and methyl glucosyl-3,4-dehydroapo-8¢-lycopenoate from Planococcus maritimus 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…9 Because methyl glucosyl-3,4-dehydro-apo-8¢-lycopenoate has a unique structure and antioxidative activity, we searched for its biosynthetic intermediates to investigate the biosynthetic pathway and to find novel antioxidative structures. For this study, we performed chemical mutagenesis with H. halophilus, and obtained mutant OC1, which shows a light orange phenotype (parent strain: deep orange).…”
Section: Introductionmentioning
confidence: 99%
“…et al Kim & Lee, 2012), and the modification of CrtNb from a diketolase to a monoketolase determines the diversion to 4-glycosyl-49-methyl-4,49-diapolycopen-49-oate fatty acid esters (Shindo et al, 2008;Osawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C 30 carotenoids are group specific, as in the case of heliobacteria (Takaichi et al, 2003) and pigmented Bacillales. Bacteria from the latter group with a well-established C 30 carotenoid pathway include Planococcus maritimus (Shindo et al, 2008), Halobacillus halophilus (Osawa et al, 2010) and Sporosarcina aquimarina (Steiger et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Not all organisms are capable of synthesising carotenoids de novo, instead their formation is restricted to the secondary metabolism of plants, algae and certain groups of fungi and bacteria [8,9]. In higher plants, algae and fungi the carotenoids produced contain a C 40 scaffold [9,10], whilst bacteria can produce a diverse range of carotenoids with both C 40 and C 30 backbones [11][12][13][14][15][16][17][18][19][20][21][22]. The origin of this structural diversity resides from the prenyl diphosphates precursors utilised in the first committed step of carotenoid biosynthesis [23].…”
Section: Introductionmentioning
confidence: 99%